2021
DOI: 10.1080/03007995.2021.1932448
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness and safety of apixaban, LMWH, and warfarin among high-risk subgroups of VTE patients with active cancer

Abstract: Objective: This pooled claims database study evaluated the risk of recurrent Venous Thromboembolism (VTE) and major bleeding (MB) among patients with VTE and active cancer prescribed apixaban, low-molecular weight heparin (LMWH), or warfarin stratified by high-risk subgroups. Methods: Patients diagnosed with VTE in the setting of active cancer who initiated apixaban, LMWH, or warfarin were identified using four US commercial claims databases from 01SEP2014 to the end of the study period (MarketScan: 01MAR2014-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
2
0
1
Order By: Relevance
“…The present study supports previous observational studies that have shown comparable bleeding rates between DOACs and LMWH, 10 , 12 , 13 thus strengthening the real-world safety of DOACs in Thailand and similar health care settings. Most real-world studies, 13 , 27 including this one, predominantly involve patients treated with rivaroxaban as it is the most used DOACs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study supports previous observational studies that have shown comparable bleeding rates between DOACs and LMWH, 10 , 12 , 13 thus strengthening the real-world safety of DOACs in Thailand and similar health care settings. Most real-world studies, 13 , 27 including this one, predominantly involve patients treated with rivaroxaban as it is the most used DOACs.…”
Section: Discussionsupporting
confidence: 90%
“…[6][7][8][9] Real-world studies have also confirmed the comparable effectiveness and safety of DOACs and LMWHs in patients with CAT. [10][11][12][13] It is important to recognize that most trials and real-world studies on CAT treatments, specifically DOACs and LMWH, have primarily been conducted in high-income countries (HICs). [10][11][12][13] This contrasts with upper-middle-income countries (UMICs) like Thailand, which face unique challenges that may hinder the adoption of these recommended treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…включены 3393 пациента, которым проводили терапию апиксабаном, 6108 пациентов, которым проводили терапию НМГ, и 4585 пациентов с онкологическими нозологиями, которым проводили терапию варфарином по поводу ВТ. Как и в приведенном метаанализе рандомизированных исследований, данные клинической практики показали, что риск повторных тромботических событий был ниже при применении апиксабана (ОР 0,61, 95% ДИ 0,47-0,81) в сравнении с НМГ, также был ниже риск развития и выраженных кровотечений (ОР 0,63, 95% ДИ 0,47-0,86), в том числе и среди пациентов с опухолями ЖКТ: в группе апиксабана 18,2 на 100 человеко-лет против 23,8 на 100 человеко-лет в группе НМГ (ОР 0,74, 95% ДИ 0,38-1,42; р=0,608) [120].…”
Section: выбор терапии втэо в онкологииunclassified